Home-based HIV counseling and testing: Client experiences and perceptions in Eastern Uganda - Kyaddondo, David; Wanyenze, Rhoda K; Kinsman, John; Hardon, Anita (BMC Public Health, 2012)
Though prevention and treatment depend on individuals knowing their HIV status, the uptake of testing remains low in Sub-Saharan Africa. One initiative to encourage HIV testing involves delivering services at home. However, doubts have been cast about the ability of Home-Based HIV Counseling and Testing (HBHCT) to adhere to ethical practices including consent, confidentiality, and access to HIV care post-test. This study explored client experiences in relation these ethical issues. Methods: We conducted 395 individual interviews in Kumi district, Uganda, where teams providing HBHCT had visited 6–12 months prior to the interviews. Semi-structured questionnaires elicited information on clients’ experiences, from initial community mobilization up to receipt of results and access to HIV services post-test. Results: We found that 95% of our respondents had ever tested (average for Uganda was 38%). Among those who were approached by HBHCT providers, 98% were informed of their right to decline HIV testing. Most respondents were counseled individually, but 69% of the married/cohabiting were counseled as couples. The majority of respondents (94%) were satisfied with the information given to them and the interaction with the HBHCT providers. Most respondents considered their own homes as more private than health facilities. Twelve respondents reported that they tested positive, 11 were referred for follow-up care, seven actually went for care, and only 5 knew their CD4 counts. All HIV infected individuals who were married or cohabiting had disclosed their status to their partners. Conclusion: These findings show a very high uptake of HIV testing and satisfaction with HBHCT, a large proportion of married respondents tested as couples, and high disclosure rates. HBHCT can play a major role in expanding access to testing and overcoming disclosure challenges. However, access to HIV services post-test may require attention.
Keywords: Home-based HIV counseling and testing,; Africa